Developmental Toxicity of Ethanolic Extracts of Leaves of Achyranthes aspera, Amaranthaceae in Rat Embryos and Fetuses - Teshome D; Tiruneh C; Berhanu L; Berihun G; Belete ZW (Dove Medical Press, 2021)
Daniel Teshome,1 Chalachew Tiruneh,1 Leykun Berhanu,2 Gete Berihun,2 Zebader Walle Belete3 1Department of Anatomy, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Environmental Health, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 3Department of Public Health, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Daniel TeshomeDepartment of Anatomy, College of Medicine and Health Sciences, Wollo University, PO. Box 1145, Dessie, EthiopiaTel +251 919158464Email danigreatt19@gmail.comIntroduction: Achyranthes aspera is one of the medicinal plants widely used for fertility control in the local health system of Ethiopia.Objective: Assessment of developmental toxicity of ethanolic extracts of leaves of Achyranthes aspera in rat embryos and fetuses.Methods: Fresh leaves were extracted by mixing the grinded powder with 70% ethanol. Then, the extract was given orally to gravid Wistar rats at doses of 250 mg/kg, 500 mg/kg and 1000 mg/kg from day 6– 12 of gestation. On gestational days 12 and 20, embryos and fetuses were examined for developmental and gross malformations.Results: On day 12 embryos, the number of implantation sites and somites in 1000 mg/kg treated rats were significantly reduced. The number of implantation sites in pair-fed control and 1000 mg/kg groups was 11.2± 0.86 and 8.34± 0.65, respectively. Retarded development of hindlimb, forelimb, optic and olfactory systems was detected at a high dose. In addition, the number of branchial bar was significantly reduced in 1000 mg/kg dose. In near-term fetuses, significant reduction of litter weight and crown–rump length was seen at 1000 mg/kg dose. Crown–rump length in pair-fed control and 1000 mg/kg treated groups was 2.82± 0.17 cm and 2.31± 0.11 cm, respectively. Fetal resorptions and deaths in 1000 mg/kg were 1.45± 0.65 and 0.81± 0.67, respectively. However, external anomalies were not detected for all offspring at all doses.Conclusion: The finding suggests that ethanolic leaf extracts of A. aspera have detrimental effects on the development of rat embryos and fetuses at a higher dose. The possible teratogenic effects were indicated with the substantial retardation in embryonic and fetal development, decrease in number of implantation sites and rise in fetal resorptions and death. Moreover, it resulted in significant reduction in litter weight and crown–rump length at a higher dose.Keywords: Achyranthes aspera, toxicity, Wistar rat, embryo, fetus